Pedagogical translanguaging in a multilingual English program in Canada: Student and teacher perspectives of challenges. (August 2020) - Galante, Angelica
Abstract: With the multi/plurilingual turn, translanguaging has been established as one of the most popular pedagogical approaches that is vehemently advocated by scholars. However, there is a paucity of studies examining the implementation of translanguaging in multilingual classrooms and potential challenges. This article reports a study examining the implementation of translanguaging in an English language program in a Canadian university. Seven teachers and 79 students participated in the study and four types of data were collected: researcher field notes, classroom observations, student diaries, and teacher interviews. Results reveal that while teachers were willing to implement pedagogical translanguaging, time to be familiar with the approach was necessary. Results also show that students engaged in spontaneous translanguaging outside of the classroom freely, but pedagogical translanguaging was more controlled and limited to the languages shared in the classroom. While the theory of translanguaging suggests the use of students' entire linguistic repertoire, they mainly relied on the L1. Moreover, it was found that naming languages, particularly minority languages, was important in multilingual classrooms so they were not deemed invisible. The article concludes with a discussion of the unique challenges of pedagogical translanguaging in multilingual classrooms, pedagogical implications, and directions for future research.